2013
DOI: 10.1089/scd.2012.0160
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Role of Focal Adhesion Modulation in Myogenic Differentiation of Human Mesenchymal Stem Cells

Abstract: We report the establishment of a novel platform to induce myogenic differentiation of human mesenchymal stem cells (hMSCs) via focal adhesion (FA) modulation, giving insights into the role of FA on stem cell differentiation. Micropatterning of collagen type I on a polyacrylamide gel with a stiffness of 10.2 kPa efficiently modulated elongated FA. This elongated FA profile preferentially recruited the b 3 integrin cluster and induced specific myogenic differentiation at both transcription and translation levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 53 publications
2
34
0
Order By: Relevance
“…48 Hence, the possible mechanism was that RhoA activation in cells on scaffolds with narrow microchannels (20-20-20 and 30-30-20), initiated clustering of focal adhesion and polymerization of stress fibers, which caused increase in cellular tension, and promoted myogenic differentiation. 6,30 On the other hand, activation of Rac1 in cells on scaffolds with wide microchannels (80-30-20) might encourage the lamellipodia formation and dendritic branching, which is in agreement with another report. 49 Therefore, these results suggested that activation of RhoA GTPase, but not Rac1, might be engaged in the microchannels induced actin cytoskeleton reorganization and subsequent myogenic lineage commitment.…”
Section: Role Of Rhoa/rock On Topography Induced Stem Cell Differesupporting
confidence: 91%
See 1 more Smart Citation
“…48 Hence, the possible mechanism was that RhoA activation in cells on scaffolds with narrow microchannels (20-20-20 and 30-30-20), initiated clustering of focal adhesion and polymerization of stress fibers, which caused increase in cellular tension, and promoted myogenic differentiation. 6,30 On the other hand, activation of Rac1 in cells on scaffolds with wide microchannels (80-30-20) might encourage the lamellipodia formation and dendritic branching, which is in agreement with another report. 49 Therefore, these results suggested that activation of RhoA GTPase, but not Rac1, might be engaged in the microchannels induced actin cytoskeleton reorganization and subsequent myogenic lineage commitment.…”
Section: Role Of Rhoa/rock On Topography Induced Stem Cell Differesupporting
confidence: 91%
“…BK121 and BK126, Cytoskeleton, Inc.) according to the vendor's instructions as reported in the literatures. 29,30 The signals were read by measuring absorbance at 490 nm using a microplate spectrophotometer (Infinite200 V R microplate reader, Tecan Inc., Maennedorf, Switzerland).…”
Section: E G-lisa Kitmentioning
confidence: 99%
“…Previous studies have drawn a network of potential mechanism through which mechanical stimulus of ECM regulates multi‐lineage specification of stem cells. Investigation of integrin, a sensor in mechanotransduction process with α and β subunits with multiple types, found β3 integrin regulated myogenic differentiation of MSCs on substrates with medium stiffness (Yu et al, ), while α5β1 integrin might mediate osteogenic commitment of MSCs (Pek, Wan, & Ying, ). Other mechanical related proteins like nuclear Lamin‐A also has been identified a close relationship between its expression induced by different stiff substrates and osteogenic/adipogenic phenotypes (Swift et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, combined with qRT‐PCR data, we demonstrated that the fibronectin stripe micropattern platform was able to direct the differentiation of bmMSC, aMSC, and fMSC specifically towards myogenic lineage. In order to compare myogenic capability between the three types of MSCs at protein level after 3 and 7 d of culture, we semiquantified the percentage of cells that showed positive MHC staining (in a total approximate cell number of 200) 62. Generally, more positive MHC staining was detected at day 7 (≈40%) than day 3 (≈20%).…”
Section: Resultsmentioning
confidence: 99%